Teorías de la Justicia y de la Legitimación: Una reivindicación de la sustantividad en las Teorías de la Justicia - Vanney, María Alejandra (Revista de Derecho, 2019)
This article discusses a general class of theories that attempt to base a normative accountof justice on consent-giving procedures. Contemporary political philosophersoffer many different accounts of justice, but at present consent-based theories areprobably the most popular. Notwithstanding their (often understandable) appeal, Iwill argue they cannot possibly succeed. All consent-based theories trade on a crucialambiguity as to whether they are supposed to be understood as voluntarist accountsof justice on the one hand, or as rationalist accounts on the other. In the formercase, consent-based theories fail because they are at best indeterminate and at worstincoherent; in the latter case, they fail because they are superfluous. I will refer tothis fatal ambiguity as “Cassirer’s Dilemma.” Interestingly, Cassirer’s Dilemma is notat all new, on the contrary, it may be among the oldest problems plaguing westernmoral and political philosophy. Faced with this insurmountable difﬁculty, I believewe ought to abandon proceduralism and focus instead on developing substantiveaccounts of justice
Keywords: Theories of justice; procedimentalism; voluntarian or rational consensualism; sustantive justice.